European stories : intellectual debates on Europe in national contexts - Lacroix, Justine; Nicolaïdis, Kalypso (Oxford ; New York : Oxford University Press, 2010)
List of Figures xii
Includes bibliographical references (p. 363-399) and index.
Keywords: European Union; Nationalism -- European Union countries; Aydınlar -- Siyasal faaliyet -- Avrupa; Milliyetçilik -- ABD; Akademisyenler -- Avrupa -- Tutumlar -- Kültürlerarası çalışmalar; Scholars -- Europe -- Attitudes -- Cross-cultural studies; Europe -- Public opinion -- Cross-cultural studies